Experimental research regarding the improvement of the selection process for the track and field middle-distance and long-distance running events - Olteanu, I.; Dobrescu, T. (Annals of the University Dunarea de Jos Galati, Fascicle XV: Physical Education and Sport Management, 2016)
This paper arrives in a context when in Romania there are several selection criteria and action directions, which, however, do not fully solve the much more complex phenomenon of directing athletes toward the middle distance and long distance running events, thus it considers that it would be beneficial to ide ntify a battery of tests for the selection, with markers that would favor the improvement of this process.The research consisted in an experiment within which batteries of tests were applied, structured on the components of the champion model, meaning the anthropometric, the functional, the psychological, and the motor skills parameters. For a better relevance of the research, performance markers were also included, with the results recorded during the area and national competitions at the time of the experiment. The selection and the direction of the 14-15 year-old athletes toward the middle distance and long distance running events constitutes an important starting point in getting the needed results, significantly shortening the road to great performances.This is confirmed by the final results of the experiment, in which the experimental group values overlap the champion values, the control group values being inferior. It is necessary for a permanent observation of the dynamics of the track and field results for the middle distance and long distance running events worldwide, in order to be able to make predictions in regards to their development and to be able to make corrections in the selection process in due time.